Landslide Learning Model Based on Physics Practicum for Disaster Awareness of Prospective Teacher Students - Wahyudi, Wahyudi; Ayub, Syahrial; Zuhdi, Muhammad; Doyan, Aris; Gunada, I Wayan (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2023)
Raising disaster awareness for student teachers has become a necessity nowadays, especially in Indonesia which is geographically located in the world's ring of fire. It is hoped that the physics practicum-based landslide learning model will be able to raise disaster awareness among prospective teachers. By using a landslide case study, this research seeks to create a disaster learning resource model that is student-oriented, including lesson plans, LKPD, syllabus, and disaster awareness evaluation. The 4D model research design—Define, Design, Develop, and Disseminate—is the research methodology used in this research. Analysis of learning objectives, disaster awareness, and disasters is completed in the Define step. Learning tools are created during the Design stage. Product development, product expert validation, product revision, and testing of methods for evaluating student instructors' knowledge of disasters are all carried out in the development stage; Product distribution has not been completed at the disseminate stage. The trial was carried out among a sample of fifteen prospective teachers from the Physics Education Study Program, FKIP, Mataram University. The expert validator test of the disaster (landslide) learning model learning tool based on practical physics gave valid results. The results of the validity and reliability test of the disaster awareness evaluation instrument are valid and reliable. These results support the idea that disaster awareness assessment instruments and learning resources for prospective teachers can be used in the classroom.